Use the zero product property to find the solitions to the equation(x+2)(x+3)=12.
1 answer:
Answer:
(x + 2) (x + 3) = x² + 3x + 2x + 6 = 12 (multiply the binomials)
(x + 2) (x + 3) = x² + 5x + 6 = 12
(x + 2) (x + 3) = x² + 5x + 6-12 = 0 (add the like term and bring the positive 12 to the other side which makes it negative)
x² + 5x + 6 = 0
Using the snowflake method - (finding the factors of 6 that adds/subtracts to give you 5).
This method will give you the factors (x + 6)(x - 1)
ZERO PROPERTY RULE:
(x + 6) = 0
x = -6
(x - 1) = 0
x = 1
The two solutions to the equation are -6 and 1.
You might be interested in
Answer:
JJKJHJKHKJHKJH
Step-by-step explanation:
Hope this helps you out . Of solving for k then just set it equal to zero
Step-by-step explanation:
work is shown and pictured
Answer: B. 4
Step-by-step explanation: Divide 20 by 5 and get 4.